Starving for Revolution: The Milwaukee Black Panther Party's Struggle to Feed the Hungry - Heynen, Nikolas C. (My University, 2006)
Lecture demonstrates how the efforts of the Milwaukee Black Panther party challenged Milwaukeeans to confront hunger among the poor and led to the formation of the Milwaukee Hunger Task Force, one of two large food banks in the region and an institutional advocate for hunger relief.
Lecture delivered on November 3, 2005 at the University of Wisconsin-Milwaukee UWM Libraries.
Keywords: Black power; Black militant organizations; Malnutrition